(untitled) (Jurnal Bahasa, 2004)
Generally, Malay vocabularies can be divided into two major groups, namely (i) native vocabularies, and (ii) foreign or borrowed vocabularies. Among the foreign words borrowed into Malay come from Chinese. Phonologically, these borrowed words demonstrate themselves in two different behaviours. First, these words will undergo phonological changes that are in agreement with the native grammatical system. Second, these borrowed words will preserve and uphold their foreign characteristics, thus their realisations are in contradiction with the grammatical system of the native language. This latter aspect of phonological behaviour is interesting because the presence of foreign elements can bring about complexity in the native grammar. Correspondingly, this paper attempts to investigate and describe the phonological behaviours of Chinese loan words that have been accepted and become parts of Malay vocabularies. The phonological aspects that come under discussion are the second phenomenon, which involves the preservation of Chinese features that are in contradiction with the Malay phonological system. The phonological aspects that will be discussed are (i) vowel harmony, (ii) homorganic nasal, (iii) vowel reduction, and (iv) vowel nasalization.